2021
DOI: 10.1002/aic.17238
|View full text |Cite
|
Sign up to set email alerts
|

Lead adsorption in a serpentine millichannel‐based packed‐bed device: Effect of hydrodynamics and mixing characteristics

Abstract: The present study depicts the hydrodynamics and the mixing characteristics in a millichannel‐based serpentine fixed‐bed device to attain the particular demands of the miniature adsorption devices' fabrication. Residence time distribution analyses were accomplished to analyze the velocity distribution inside the packed bed geometry. The effects of operating variables on the system hydrodynamics and mixing and their impact on the lead adsorption characteristics were enunciated. New correlations were proposed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 81 publications
1
8
0
Order By: Relevance
“…The RTD curves become sharper at the greater flow rate, which represents the lower mean residence time ( t m ) for the single‐phase flow (Figure 2A). The RTD curves become broader when the channel dispersion number, which is the Peclet number's reversal, increases, as shown in Figure 2A 44–46 . In the case of the two‐phase flow, when the flow rate of one phase increases, leaving the other unaltered, the residence time decreased, and the RTD curves become sharper due to the increment of the velocity of the phases (Figure 2B,C).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The RTD curves become sharper at the greater flow rate, which represents the lower mean residence time ( t m ) for the single‐phase flow (Figure 2A). The RTD curves become broader when the channel dispersion number, which is the Peclet number's reversal, increases, as shown in Figure 2A 44–46 . In the case of the two‐phase flow, when the flow rate of one phase increases, leaving the other unaltered, the residence time decreased, and the RTD curves become sharper due to the increment of the velocity of the phases (Figure 2B,C).…”
Section: Resultsmentioning
confidence: 93%
“…The RTD curves become broader when the channel dispersion number, which is the Peclet number's reversal, increases, as shown in Figure 2A. [44][45][46] In the case of the twophase flow, when the flow rate of one phase increases, leaving the other unaltered, the residence time decreased, and the RTD curves become sharper due to the increment of the velocity of the phases (Figure 2B,C). When the height of the packed channels (uniform packing materials and the bed porosity) decrease, for a particular flow rate of the fluids, the velocities and the mixing properties of the phases increased, lowing the residence time, and making the RTD sharper (Figure 2B,C).…”
Section: Velocity Distribution Modelmentioning
confidence: 96%
“…Mondal et al reported that the tracer residence time increased at a lower flow rate, which also broadened the residence time distribution curve. 35 This was due to the fact that the diffusive process dominated at a lower flow rate. Furthermore, the residence time distribution density function curve did not exhibit a trailing tail, which implied that there was almost no dead zone in the packed region.…”
Section: Resultsmentioning
confidence: 99%
“…The correlation was determined via least-squares fitting as follows There was an almost inverse proportional relationship between the mean residence time and inlet velocity. Similarly, Mondal et al 35 investigated the mean residence time in the millichannel-based fixed-bed device for different flow rates. Based on their experimental data, the relationship between mean residence time and flow rate was …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation